2017
DOI: 10.1007/s12035-016-0351-z
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Autophagy in the Correlation Between Neuron Damage and Cognitive Impairment in Rat Chronic Cerebral Hypoperfusion

Abstract: Pathological changes and cognitive impairment caused by chronic cerebral hypoperfusion (CCH) have been previously reported. However, how these changes progress remains unclear. Additionally, there are few studies regarding the mechanism underlying the involvement of autophagy in these processes. Two-step bilateral common carotid artery occlusion (BCCAO) was performed to replicate CCH in Sprague Dawley rats. The animals were divided into seven groups, including a sham group and 2-, 4-, 8-, 12-, 16-, and 20-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 61 publications
7
40
0
Order By: Relevance
“…Subsequently, these rats exhibit clinically relevant characteristics of T2DM were further subjected to BCCAO surgery, which has been widely used to constitute the pathological condition of CCH. Our study found that CBF decreased significantly by more than 70% immediately after BCCAO, comparable with that observed in clinical patients [18]. Additionally, we found that compared with the CCH group, CBF decrease was more pronounced in the DM-CCH group, but without statistical difference.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Subsequently, these rats exhibit clinically relevant characteristics of T2DM were further subjected to BCCAO surgery, which has been widely used to constitute the pathological condition of CCH. Our study found that CBF decreased significantly by more than 70% immediately after BCCAO, comparable with that observed in clinical patients [18]. Additionally, we found that compared with the CCH group, CBF decrease was more pronounced in the DM-CCH group, but without statistical difference.…”
Section: Discussionsupporting
confidence: 89%
“…Neuronal degeneration and memory deficits caused by CCH have been extensively reported [7,30]. Consistently, we have previously found that neuronal injury and cognitive impairment are prominent at 8 weeks following BCCAO [18]. Similarly, studies also found that STZ-induced DM could aggravate neuronal apoptosis and cognitive dysfunction in rodents [31].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Autophagy, which is an adaptive reaction of cells to stress produced by alterations in the internal and external environments, is a dynamic catabolic process involved in multiple cellular processes (21). However, excessive autophagy may trigger cell death and contribute to ischemia-induced neuronal damage (22,23). Inhibition of autophagy has thus demonstrated beneficial effects in modulating neurological deficits following cerebral ischemia (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal pyknosis detected by HE staining has widely been used as a marker for neuronal degeneration after ischemic brain damage recently [45]. To evaluate neuronal degeneration, we examined neuronal pyknosis with HE staining and analyzed mRNA expression of apoptosis genes.…”
Section: Neuronal Degenerationmentioning
confidence: 99%